Diversity and adaptation properties of actinobacteria associated with Tunisian stone ruins - Saadouli, Ilhem; Marasco, Ramona; Mejri, Lassaad; Hamden, Haytham; Guerfali, Meriem M’saad; Stathopoulou, Panagiota; Daffonchio, Daniele; Cherif, Ameur; Ouzari, Hadda-Imene; Tsiamis, George; Mosbah, Amor (Frontiers in Microbiology, 2022)
Stone surface is a unique biological niche that may host an abundant microbial diversity. However, microbial growth is regulated by the stressful and fluctuating thermal, moisture, and nutritional conditions associated with the stones. The exploration of the biodiversity of the stone microbiome represents a major challenge and an opportunity to characterise new strains equipped with valuable biological activity. Here, we explored the diversity and adaptation strategies of bacterial communities associated with Roman stone ruins in Tunisia by considering the effects of geo-climatic regions and stone geochemistry. Amplicon sequencing showed that stone bacterial communities were dominated by three phyla, including Cyanobacteria, Proteobacteria, and Actinobacteria, and their members were differentially distributed according to the geo-climatic origin. Stone geochemistry, particularly the availability of magnesium, chromium, and copper, also influenced the bacterial communities’ diversity. Cultivable actinobacteria were further investigated to evaluate the adaptative strategies adopted to survive in/on stones. All the cultivated bacteria belonged to the Actinobacteria class, and the most abundant genera were Streptomyces, Kocuria and Arthrobacter. They were able to tolerate high temperatures (up to 45°C) and salt accumulation, and they produced enzymes involved in nutrients’ solubilisation, such as phosphatase, amylase, protease, chitinase, and cellulase. Actinobacteria members also had an important role in the co-occurrence interactions among bacteria, favouring the community interactome and stabilisation. Our findings provide new insights into actinobacteria's diversity, adaptation, and role within the microbiome associated with ruins’ stones. We also highlight how members of this group of bacteria can have great potential for agricultural, biotechnological, biopharmaceutical, and biocontrol applications.